2006
DOI: 10.1098/rspb.2006.3661
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of an asexual American water flea clone throughout Africa and rapid displacement of a native sibling species

Abstract: The huge ecological and economic impact of biological invasions creates an urgent need for knowledge of traits that make invading species successful and factors helping indigenous populations to resist displacement by invading species or genotypes. High genetic diversity is generally considered to be advantageous in both processes. Combined with sex, it allows rapid evolution and adaptation to changing environments. We combined paleogenetic analysis with continent-wide survey of genetic diversity at nuclear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(159 citation statements)
references
References 45 publications
7
150
0
Order By: Relevance
“…Our results suggest that further investigation are advisable in order to verify whether the current population is the last remnant of a once much larger metapopulation eventually reduced by anthropogenic disturbances (e.g., fish introductions, water contamination with toxic chemicals) or if it represents the invasion of North American strains that have recently colonised large parts of New Zealand, Africa and Spain, and that was already recorded in Northern Italy and Sardinia (Mergeay et al, 2006; Vergilino et al, 2011;Duggan et al, 2012;Crease et al, 2012;Markova et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that further investigation are advisable in order to verify whether the current population is the last remnant of a once much larger metapopulation eventually reduced by anthropogenic disturbances (e.g., fish introductions, water contamination with toxic chemicals) or if it represents the invasion of North American strains that have recently colonised large parts of New Zealand, Africa and Spain, and that was already recorded in Northern Italy and Sardinia (Mergeay et al, 2006; Vergilino et al, 2011;Duggan et al, 2012;Crease et al, 2012;Markova et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The identity of European and American populations of morphologically similar species may be doubtful (Hrbacek, 1987). The accumulation of genetic data has showed that North American and European D. pulex are genetically two distinct species and nomenclature of the D. pulex complex is not resolved (Colbourne et al, 1998;Palsoon, 2000;Mergeay et al, 2006;Petrusek et al, 2008;Crease et al, 2012;Markova et al, 2013). Even in Europe, asexual strains of D. pulex show a more northerly distribution than sexual ones (Ward et al, 1994;Weider and Hobaek, 1997) and both lineages may co-exist within the same geographical region (Letho and Haag, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…80 years (yrs), belonging to a north American haplotype (Mergeay et al, 2006, Crease et al, 2012. Hence, the current South African D. pulex is most likely an exotic hybrid that has replaced a native D. pulex, which was closer to the European populations (Mergeay et al, 2006 (Sars, 1916;Fig. 10), which is found also in East Africa (Löffler, 1968, Mergeay et al, 2005, wide molecular surveys (De Gelas and De Meester, 2005) have not taken the South African populations into account, therefore we cannot speculate on their origin.…”
Section: Neglected South African Taxa: the Example Of Daphniamentioning
confidence: 97%
“…ulations of D. pulex on the African continent actually are pulex x pulicaria hybrids that have been introduced and expanded throughout the continent over a period of ca. 80 years (yrs), belonging to a north American haplotype (Mergeay et al, 2006, Crease et al, 2012. Hence, the current South African D. pulex is most likely an exotic hybrid that has replaced a native D. pulex, which was closer to the European populations (Mergeay et al, 2006 (Sars, 1916;Fig.…”
Section: Neglected South African Taxa: the Example Of Daphniamentioning
confidence: 99%
“…Paleolimnological studies on the population genetics of water fleas in such lakes show that their genotypic identity is stable through time as long as episodes of ecological crisis (such as lake desiccation) do not exceed the few decades during which resting eggs remain viable in bottom muds (Mergeay et al, 2007). Another paleogenetic study (Mergeay et al, 2006) revealed that an asexual American variant of the common water flea Daphnia pulex, introduced accidentally to Lake Naivasha in Kenya in the 1920s, has since outcompeted the indigenous, sexually reproducing variant of the same species not only locally, but throughout sub-Saharan Africa (Fig. 2).…”
Section: Resolving Human Impact On African Ecosystemsmentioning
confidence: 99%